“Elaboración de barras a partir de pulpa de taperiba (spondias dulcis P.) y su utilización en tabletas de chocolate - Gutiérrez Castillo, Lucero Margarita (2004)
This research work proposes an industrial altemative for cultivation of taperiba (Spondias dulcis P) by determining the suitable technological parameters of dry bars processing from taperiba pulp, in such way fits to desired characteristics for its use in stuffed chocolate; it was evaluated its organoleptical characteristics, proximate chemical analysis; as well as, pulp/chocolate relationship, from taperiba bars obtained with pulp of: 15ºBrix (in addition of sugar 0%), standardized on 25ºBrix, and 35ºBrix, they have presented moistures of 20%, 25% and 30%. To determine the drying temperature, that was realized out a preliminary test comparing taperiba bars elaborated with pulp without addition of sugar obtained with dried temperatures of: 40ºC, 45ºC and 50ºC until moisture 30%, being taperiba bar obtained with a dried temperature of 40ºC, which presented best general appearance; as well as a major preservation on vitamin C [40ºC (19.3%), 45°(18.45%), 50ºC (17.23%)] is for which took an dried temperature of 40ºC, respectively. On the other hand, sensorial analysis determined that best treatment is taperiba bar with moisture 30% so much for pulp elaborated bar no addition of sugar l 5ºijrix, standardized on 25ºBrix and 35ºBrix, since they reached major seores to preserve best the taperiba organoleptical characteristics. To determine adequate ºBrix on the pulp for processing of taperiba bar compared the results of sensory evaluation along with proximate chemical analysis of the bars elaborated bars without addition of sugar 15ºBrix, with standardized pulp on 25ºBrix and 35ºBrix. Finding that best treatment for obtainment of taperiba bars is adding on pulp 13% of sugar reaching 25ºBrix and to dry it with a temperature 40ºC along with a time of 28 hours until to get a moisture 30%, because this presented good organoleptical characteristics and an empire yellow color (22.5% orange, 67.9% yellow and 9.5% white) reinforcing these results, with proximate chemical analysis obtaining the following results: protein 0.81 %, vitamin C 17.6%, carbohydrates 63%, respectively. Taperiba bars obtained with 30% moisture and elaborated with pulp {l 5ºBrix), standardized on 25ºBrix and 35ºBrix; were coated in chocolated milk under bonbons presentation, evaluating their acceptability through a panel of 12 judges being taperiba bar elaborated with standardized pulp on 25ºBrix and coated with chocolated milk that presented good acceptability on sensory test, not existing significant difference to the 5% probability with pulp elaborated bar standardized on 35ºBrix. The bar pulp standardized on 25ºBrix utilizes wess dry time (28 hours ), representing a raw material saving and machine-hour during dry process. Sensory test determined that stuffed chocolate with 20% of taperiba bar pieces was the best treatment since it obtained major proportional acceptability and best organoleptical characteristics, besides having good physical-chemical properties: moisture 3.43%, protein 5.31%, fat 25.35%, fibre 1.14%, carbohydrate 63.12%, vitamin C17.6%. It was realized out its microbiological analysis of which values are within range recommended by DIGESA, which has been demonstrated the quality and harmlessness ofthe product.